High-Efficiency Sky Blue-To-Green Fluorescent Emitters Based on 3-Pyridinecarbonitrile Derivatives - Masuda, Yuki; Sasabe, Hisahiro; Arai, Hiroki; Onuma, Natsuki; Kido, Junji (Frontiers in Chemistry, 2019)
The pyridinecarbonitrile derivative is well known as an acceptor unit in fluorescent materials. However, its use in thermally activated fluorescent emitters (TADF) is very limited compared with the benzenecarbonitile counterparts. Very recently, we developed a series of 4-pyridinecarbonitrile, so-called isonicotinonitrile derivatives, as a highly efficient sky blue-to-green TADF emitters realizing low-drive-voltage OLEDs. In this work, we contributed new design and development for three types of 3-pyridinecarbonitrile-based TADF emitters named 2AcNN, 2PXZNN, and 5PXZNN. Among these emitters, a green emitter, 2PXZNN realized a highly efficient TADF OLED with a maximum external quantum efficiency of over 20%.